Functional outcome of an arthroscopic anatomical single bundle anterior Cruciate Ligament (ACL) reconstruction using Semi-tendinosus graft with fixation using Endo-button on femoral side and Suture Disc on Tibial side- A prospective clinical study - Jagtap, Vinod; Gorgile, Namdev; Shah, Yash; Rokade, Vikas; Bartakke, Girish (International Journal of Research in Orthopaedics, 2017)
Background: Injury to the anterior cruciate ligament (ACL) is one of the most frequent injuries of the knee during different sports activities. Arthroscopic surgical reconstruction is the current standard of care for treatment of ACL injuries in young and active patients. The widespread adoption of ACL reconstruction over primary repair was based on early perception of the limited healing capacity of the ACL. Hamstring tendon is most favoured graft for ACL reconstruction. We wanted to study the outcomes particular method of fixation for fixing the hamstring tendon. Methods: In this study 30 patient with ACL injury were treated arthroscopically for the fixation of graft in bone tunnel we use endobutton for femur and suture disc for tibia as suspensor implant and prospective assessment of functional outcome using Tegner Lysholm knee scoring system. Results: The preoperative activity level could be maintained in 70% of the patients. The Lysholm score showed very good and good results in 80%. Functional and stability results in about 70% of the patients. Conclusions:This surgical technique can be recommended for the active patient with ACL deficiency. The functional outcome of anterior cruciate ligament reconstruction with quadrupled semitendinosus tendon autograft using Endobutton and suture disc is good. This method of fixation will help the graft to facilitate graft tunnel healing and also maintain its strength until there is a good graft to bone healing occurs completely.